Size Classification of Tomato Fruit Using Thresholding, Machine Learning, and Deep Learning Techniques - Robert G. de Luna; Elmer P. Dadios; Argel A. Bandala; Ryan Rhay P. Vicerra (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The size of tomato fruits is closely related to the market segment and price. Manual sorting in tomato is very dependent on human interpretation and thus, very prone to error. The study presents thresholding, machine learning, and deep learning techniques in classifying the tomato as small, medium, and large based from a single tomato fruit image implemented using Open CV libraries and Python programming. Tomato images with different sizes are gathered where features like area, perimeter, and enclosed circle radius are extracted. The experiment shows that using thresholding, a classification accuracy of 85.83%, 65.83%, and 80% was achieved for area, perimeter, and enclosed circle radius, respectively. For machine learning, the training accuracy rates were recorded as 94.00%-95.00% for SVM, 97.50-92.50% for KNN and 90.33-92.50% for ANN. Comparison of models revealed that SVM is the most model without over fitting. The deep learning approach, regardless of the algorithm, produced low performances with 82.31%-78.21%-55.97% training-validation-testing accuracy for VGG16, 48.17%-41.44%-37.64% for InceptionV3, and 56.05%-44.96%-22.78% for ResNet50 models. Comparative analysis showed that machine learning technique bested the performance of the thresholding and deep learning techniques in classifying the tomato fruit size in terms of accuracy performance.